Emotional exhaustion and deviant behaviors with self-efficacy as a moderating variable - Rian Ekta Bion Abdi; Syahrizal Syahrizal (Universitas Negeri Padang, 2021)
This study was to analyze: (1) The effect of emotional exhaustion on deviant behavior in nurses in the Army Hospital dr. Reksodiwiryo Padang. (2) The effect of emotional exhaustion on deviant behavior with self-efficacy as a moderating variable in nurses in the Army Hospital dr. Reksodiwiryo Padang. This type of research is a causative descriptive study. The study population was all nurses in inpatient at the Army Hospital dr. Padang Reksodiwiryo, amounting to 146 people. While the number of research samples is determined based on the cluster proportional sampling method with a sample of 107 people. The data used are primary and secondary data. The analysis technique used is descriptive and inductive analysis through Moderated Regression Analysis (MRA) analysis using SPSS Version 17.00. The results showed that: (1) emotional exhaustion had a positive and significant effect on deviant behavior in nurses in the Army Hospital dr. Reksodiwiryo Padang. (2) the self-efficacy variable does not weaken the influence between emotional fatigue on deviant behavior in nurses in the Army Hospital dr. Reksodiwiryo Padang.